Metabolic, behavioural, and psychosocial risk factors and cardiovascular disease in women compared with men in 21 high-income, middle-income, and low-income countries: an analysis of the PURE study. Issue 10355 (10th September 2022) - Walli-Attaei, Marjan; Rosengren, Annika; Rangarajan, Sumathy; Breet, Yolandi; Abdul-Razak, Suraya; Sharief, Wadeia Al; Alhabib, Khalid F; Avezum, Alvaro; Chifamba, Jephat; Diaz, Rafael; Gupta, Rajeev; Hu, Bo; et al.
Summary: Background: There is a paucity of data on the prevalence of risk factors and their associations with incident cardiovascular disease in women compared with men, especially from low-income and middle-income countries. Methods: In the Prospective Urban Rural Epidemiological (PURE) study, we enrolled participants from the general population from 21 high-income, middle-income, and low-income countries and followed them up for approximately 10 years. We recorded information on participants' metabolic, behavioural, and psychosocial risk factors. For this analysis, we included participants aged 35–70 years at baseline without a history of cardiovascular disease, with at least one follow-up visit. The primary outcome was a composite of major cardiovascular events (cardiovascular disease deaths, myocardial infarction, stroke, and heart failure). We report the prevalence of each risk factor in women and men, their hazard ratios (HRs), and population-attributable fractions (PAFs) associated with major cardiovascular disease. The PURE study is registered with ClinicalTrials.gov, NCT03225586. Findings: In this analysis, we included 155 724 participants enrolled and followed-up between Jan 5, 2005, and Sept 13, 2021, (90 934 [58·4%] women and 64 790 [41·6%] men), with a median follow-up of 10·1 years (IQR 8·5–12·0). At study entry, the mean age of women was 49·8 years (SD 9·7) compared with 50·8 years (9·8) in men. As of data cutoff (Sept 13, 2021), 4280 major cardiovascular disease events had occurred in women (age-standardised incidence rate of 5·0 events [95% CI 4·9–5·2] per 1000 person-years) and 4911 in men (8·2 [8·0–8·4] per 1000 person-years). Compared with men, women presented with a more favourable cardiovascular risk profile, especially at younger ages. The HRs for metabolic risk factors were similar in women and men, except for non-HDL cholesterol, for which high non-HDL cholesterol was associated with an HR for major cardiovascular disease of 1·11 (95% CI 1·01–1·21) in women and 1·28 (1·19–1·39) in men, with a consistent pattern for higher risk among men than among women with other lipid markers. Symptoms of depression had a HR of 1·09 (0·98–1·21) in women and 1·42 (1·25–1·60) in men. By contrast, consumption of a diet with a PURE score of 4 or lower (score ranges from 0 to 8), was more strongly associated with major cardiovascular disease in women (1·17 [1·08–1·26]) than in men (1·07 [0·99–1·15]). The total PAFs associated with behavioural and psychosocial risk factors were greater in men (15·7%) than in women (8·4%) predominantly due to the larger contribution of smoking to PAFs in men (ie, 1·3% [95% CI 0·5–2·1] in women vs 10·7% [8·8–12·6] in men). Interpretation: Lipid markers and depression are more strongly associated with the risk of cardiovascular disease in men than in women, whereas diet is more strongly associated with the risk of cardiovascular disease in women than in men. The similar associations of other risk factors with cardiovascular disease in women and men emphasise the importance of a similar strategy for the prevention of cardiovascular disease in men and women. Funding: Funding sources are listed at the end of the Article.